Public Stigma of Autism Spectrum Disorder at School: Implicit Attitudes Matter. - Aubé, Benoite; Follenfant, Alice; Goudeau, Sébastien; Derguy, Cyrielle (Journal of Autism & Developmental Disorders, 2021)
This study examines the public stigma of children with autism spectrum disorder (ASD) by their school-aged peers, focusing on both explicit and implicit attitudes. The twofold aims were to provide a broader picture of public stigma and to explore age-related changes in attitudes. Students completed an explicit measure of the public stigma and an implicit measure of attitudes after watching a video displaying children with ASD vs. typically developing (TD) children. Both measures showed more negative perceptions towards children with ASD compared to TD children. However, while explicit attitudes improved with age, implicit attitudes remained constantly negative. This finding suggests that both explicit and implicit attitudes should be considered when promoting an inclusive climate at school.